IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI KURIKULUM MERDEKA DALAM PEMBELAJARAN EKONOMI: IDENTIFIKASI HAMBATAN DAN SOLUSI (STUDI KASUS SMA NEGERI 1 SURAKARTA) - Wahyu Mei; Synta Febriani; Siti Fatimah; Sri Prihatin Susilaningsih; Muhammad Sabandi (Universitas Muhammadiyah Metro, 2025)
Differentiated learning is a learning strategy implemented in the Merdeka Curriculum at almost all levels of education. However, in reality, the application of differentiated learning has not been implemented optimally. This case study aims to describe the obstacles and solutions in implementing differentiated learning in economics learning at SMA Negeri 1 Surakarta. The subjects in this study focus on teachers at SMA Negeri 1 Surakarta. A descriptive qualitative approach with a case study design was used in this study. Data were collected using observation, interview, and documentation methods. The results of this study show that the implementation of differentiated learning in economic learning has not been fully implemented due to the limited time for preparation and learning process, limited resources, the complexity of the material taught, and the low level of teacher readiness. These obstacles can be overcome with alternative solutions that can be seen from the teacher and learning side. From the teacher's side, teachers must try to understand the characteristics of students and teachers can multiply references to differentiated learning models through social media and collaborate with other teachers, then from the learning side, among others, differentiated learning should prioritize the quality of the learning process, assessment-based learning, learning that provides a content, process, and product approach, learning is learner-centered, and the government can provide training for teachers. This study needs to expand its subjects so that the results are more representative of the actual situation.